TRANSFORMASI MASYARAKAT INDONESIA PADA MASA PENJAJAHAN BANGSA BARAT - Nurmalasyari, Nurmala; Wulandari, Nadila; Amalia Putri, Winda (CV. Kalimasada Group, 2024)
This study aims to analyze labor dynamics in the archipelago during the Transformation Of Indonesian Society In The Period Colonization Of Western Nations, This research uses a literature study using books and research articles as reference material. The presence of Europeans: Portuguese, Spanish, Dutch and British have changed the landscape of Indonesian society. Impact of Colonization : Changes in social structures, shifts in cultural values, economic dependence, and the emergence of popular resistance in various regions. In order to understand the extent of the transformation that occurred, it is necessary to compare the conditions of Indonesian society before and after the arrival of the colonialists. The return of western colonialists left a positive and negative legacy for Indonesian society.